Transformation of Chaetomium globosum with hygromycin B resistance plasmids pCB1003 - CHEN Zhen-ming; GUO Ze-jian; LIN Fu-cheng; LI De-bao (浙江大学学报. 农业与生命科学版, 2001)
Genetic transformation has been achieved by incubating protoplasts from Chaetomium globosum with plasmid PCB1003. The efficiency was 1-2 transformants/μg vector DNA. Protoplasts were produced by treating 14-hour old mycelium of Chaetomium globosum with 10 mg/mL lysozyme. Chaetomium globosum growth was inhibited completely when the medium contained 150 μg/mL hygromycin B. Integration of hph gene was verified by PCR and PCR product hybridization analysis. There was no evidence of mitotic of hygromycin B resistance in the transformants.